2006
DOI: 10.1002/mds.20928
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and polyneuropathy

Abstract: of a levodopa-nonresponsive PD patient who failed to improve after pallidotomy also failed to improve after DBS STN. 10 Our patients were all levodopa-responsive and, aside from a single patient, improved after their pallidotomy.There are several reasons why postpallidotomy STN DBS may result in less robust motor improvement. First, there is an obvious referral bias toward patients who were not satisfied after their pallidotomy, either for objective or subjective reasons. This may represent a more aggressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 15 publications
4
60
0
5
Order By: Relevance
“…The patient declined quantitative sensory testing and a skin biopsy for analysis of intraepidermal nerve fibers. The patient met clinical criteria, including length-dependent symptoms consistent with small-fiber damage without largefiber involvement, together with autonomic signs, for probable small-fiber neuropathy Lauria et al, 2012), and was also given a diagnosis of restless legs syndrome (Rios Romenets and Postuma, 2013), which is well established as a concomitant of painful neuropathy (Iannaccone et al, 1995;Polydefkis et al, 2000;Gemignani et al, 2006). Tizanidine and amitriptryptiline did not provide relief, and acetaminophen provided partial relief.…”
Section: R1279p Mutationmentioning
confidence: 99%
“…The patient declined quantitative sensory testing and a skin biopsy for analysis of intraepidermal nerve fibers. The patient met clinical criteria, including length-dependent symptoms consistent with small-fiber damage without largefiber involvement, together with autonomic signs, for probable small-fiber neuropathy Lauria et al, 2012), and was also given a diagnosis of restless legs syndrome (Rios Romenets and Postuma, 2013), which is well established as a concomitant of painful neuropathy (Iannaccone et al, 1995;Polydefkis et al, 2000;Gemignani et al, 2006). Tizanidine and amitriptryptiline did not provide relief, and acetaminophen provided partial relief.…”
Section: R1279p Mutationmentioning
confidence: 99%
“…31 These observations and suggestions indicate a possible link between chronic pain and RLS predisposition in patients with BD. RLS is common in cases of acquired polyneuropathy, 32 and BD is known to induce neuropathy, 33,34 suggesting that BD and RLS may be related via BD-induced polyneuropathy. The present study found no relationship between the severity of RLS (as determined by IRLSSG-RS questionnaire) and gender, BMI, clinical features of BD, or blood levels of iron, ferritin, haemoglobin, and MCV.…”
Section: Discussionmentioning
confidence: 99%
“…48 Since some of these comorbidities are also more frequent in migraine, this would be an interesting point for the investigation of the causal relationship between the two diseases. 49 A curious topic is the treatment of RLS and its possible relationship with migraine.…”
Section: Restless Legs Syndromementioning
confidence: 99%